Share this : the social media handbook for PR professionals - Waddington, Stephen (John Wiley & Sons Ltd, 2012)
Share This & nbsp;is a practical handbook to the biggest changes taking place in the media and its professions by the Chartered Institute of Public Relations (CIPR) Social Media Panel. The book was conceived and written by more than 20 public relations practitioners representing a cross-section of public, private and voluntary sector expertise using many of the social tools and techniques that it addresses. The book is split into 26 chapters over eight topic areas covering the media and public relations industry, planning, social networks, online media relations, monitoring and measurement, skill.